2015
DOI: 10.1002/jor.22915
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and symmetry patterns during the drop vertical jump, 6‐months after first‐time lateral ankle sprain

Abstract: To evaluate the adaptive movement and motor control patterns of a group with a 6-month history of first-time lateral ankle sprain (LAS) injury during a drop vertical jump (DVJ) task. Fifty-one participants with a 6-month history of first-time acute LAS injury and twenty controls performed a DVJ task. 3D kinematic and sagittal plane kinetic profiles were plotted for the lower extremity joints of both limbs for the drop jump (phase 1) and drop landing (phase 2) phases of the DVJ. Inter-limb symmetry and the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
(90 reference statements)
2
17
0
1
Order By: Relevance
“…Our kinematic results in the sagittal plane were consistent with findings of previous studies [18,20]. Although our jump task differs from those of Doherty et al [18,19], we also found that the ankle joint position in the sagittal plane differs between ankle sprain patients and healthy controls before and after landing. Our findings indicate that ankle mobility should be treated during rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our kinematic results in the sagittal plane were consistent with findings of previous studies [18,20]. Although our jump task differs from those of Doherty et al [18,19], we also found that the ankle joint position in the sagittal plane differs between ankle sprain patients and healthy controls before and after landing. Our findings indicate that ankle mobility should be treated during rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, drop landing is a highly controlled laboratory task that consists only of the eccentric phase of the jump landing cycle, whereas forward jump landing consists of a concentric (take-off) and an eccentric (landing) phase, such as athletes commonly practice in sports [35]. In (acute) ankle sprain patients, a reduced ankle plantar flexion was found while performing a bipedal drop vertical jump 2 weeks as well as 6 months after the initial injury compared to those in healthy controls [18,19]. Our kinematic results in the sagittal plane were consistent with findings of previous studies [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…15 The increased hip-joint stiffness in the CAI group reflected a hip-dominant movement strategy during the side-cutting task. Researchers have provided evidence that a hip-dominant movement strategy was used by individuals in the acute 10,11,29 and chronic [15][16][17][18]21 stages of LASs. Whereas the cause of this longitudinal dynamic-movement adaptation is unknown, the evidence suggested that a hipdominant movement strategy was used at various stages after an LAS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that muscle strength asymmetry results in asymmetry during a vertical jump [32]. Therefore, the evaluation of asymmetry in athletes is not only based on the evaluation of muscle strength but also on the ground reaction force recorded during various types of vertical jumps [33,34,35,36]. Therefore, a comprehensive evaluation of asymmetry in running is needed.…”
Section: Introductionmentioning
confidence: 99%